Biocompatibility of nickel titanium versus nitrided nickel titanium in bone and bone marrow of male New Zealand rabbits. Issue 3 (September 2015) - Mohamed, Doha S.; Lotfy, Khlaed M.
Abstract : Background: The most attractive feature of nickel titanium (NiTi) is its capability to recover its original shape after large deformations induced by mechanical load. The response of individual cells to material can be considered to be dependent on how well the material mimics the natural (extracellular) environment of the cell. Some special treatments have been reported to improve the corrosion behavior of NiTi – for example, thermal oxidation and titanium nitride coatings. Aim: The aim of the present study was to compare the biocompatibility of NiTi alloys and nitride NiTi, and to evaluate the possible toxic effect of each metal alloy on the bone and bone marrow. The study also aimed to show the role of titanium nitride coating in minimizing the corrosion of NiTi medical alloy. Materials and methods: Fifteen New Zealand male rabbits were used in this study. The rabbits were divided into three groups of five animals each. Group I was used as the control group. Rabbits in group II were implanted with NiTi alloys, and the animals in group III were implanted with nitrided NiTi. Radiological and histological studies of bone and bone marrow were performed. Results: Bone atrophy at the site of implantation and manifested bone and bone marrow affection were observed in the group implanted with NiTi medical alloys compared with the group implanted with nitrided NiTi medical alloys. Conclusion: The use of a nitride coat for NiTi medical alloys is beneficial to enhance fracture healing without affection of the surrounding bone and bone marrow.